2014
DOI: 10.2535/ofaj.90.79
|View full text |Cite
|
Sign up to set email alerts
|

Morphology of the lingual papillae in the fishing cat

Abstract: Summary:We examined the dorsal lingual surface of an adult fishing cat (Prionailurus viverrinus) by scanning electron microscopy. The filiform papillae on the lingual apex had several pointed processes. The connective tissue core of the filiform papillae resembleda a well in shape. The filiform papillae on the anterior part of the lingual body were large and cylindrical in shape. The connective tissue core of the filiform papillae consisted of a large conical papilla. The filiform papillae on the central part … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
20
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 13 publications
(27 reference statements)
1
20
1
Order By: Relevance
“…In puma, the dorsal surface of the lingual apex and body was entirely covered by filiform papillae that was reported in many carnivorous species such as bear (Pastor et al, 2011), jaguar (Emura, Okumura & Chen, 2013), ferret (Takemura et al, 2009), opossum (Okada & Schraufnagel, 2005) and fishing cat (Emura & Okumura, 2014). In the present study, filiform papillae had many secondary projections that emerged from the base of main papillae.…”
Section: Discussionsupporting
confidence: 77%
See 3 more Smart Citations
“…In puma, the dorsal surface of the lingual apex and body was entirely covered by filiform papillae that was reported in many carnivorous species such as bear (Pastor et al, 2011), jaguar (Emura, Okumura & Chen, 2013), ferret (Takemura et al, 2009), opossum (Okada & Schraufnagel, 2005) and fishing cat (Emura & Okumura, 2014). In the present study, filiform papillae had many secondary projections that emerged from the base of main papillae.…”
Section: Discussionsupporting
confidence: 77%
“…However, the lingual papillae appeared solely on the dorsal and lateral lingual surface in bears (Pastor et al, 2011). In puma, the filiform papillae on the rostral part of the lingual body were large and had a cylindrical shape, which was also reported in the rostral part of the lingual body of the fishing cat (Emura & Okumura, 2014) and the central region of the lingual body of panther (Emura et al, 2001). Additionally, these papillae were described as giant club-shaped filiform papillae on the tiger tongue (Emura et al, 2004).…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…Many studies have reported on the structures of the lingual surfaces of various animals. Scanning electron microscopy (SEM) studies have been conducted on the tongues of the cat (Boshell et al, 1982), dog (Iwasaki and Sakata, 1985), mongoose (Iwasaki et al, 1987), Japanese weasel (Furubayashi et al, 1989), sea otter (Shimoda et al, 1996), bush dog (Emura et al, 2000), panther and Asian black bear (Emura et al, 2001), lion (Emura et al, 2003), tiger (Emura et al, 2004), jaguar (Emura et al, 2013), fishing cat (Emura et al, 2014), and black-backed jackal (Emura et al, 2014) belonging to the order Carnivora. Such studies have revealed variations in the morphology and distribution of papillae on the dorsal lingual surface among these species.…”
mentioning
confidence: 99%